Unprecedented Inversion of Selectivity and Extraordinary Difference in the Complexation of Trivalent f Elements by Diastereomers of a Methylated Diglycolamide. Issue 21 (20th March 2019) - Wilden, Andreas; Kowalski, Piotr M.; Klaß, Larissa; Kraus, Benjamin; Kreft, Fabian; Modolo, Giuseppe; Li, Yan; Rothe, Jörg; Dardenne, Kathy; Geist, Andreas; Leoncini, Andrea; Huskens, Jurriaan; et al.
Abstract: When considering f elements, solvent extraction is primarily used for the removal of lanthanides from ore and their recycling, as well as for the separation of actinides from used nuclear fuel. Understanding the complexation mechanism of metal ions with organic extractants, particularly the influence of their molecular structure on complex formation is of fundamental importance. Herein, we report an extraordinary (up to two orders of magnitude) change in the extraction efficiency of f elements with two diastereomers of dimethyl tetraoctyl diglycolamide (Me2 ‐TODGA), which only differ in the orientation of a single methyl group. Solvent extraction techniques, extended X‐ray absorption fine structure (EXAFS) measurements, and density functional theory (DFT) based ab initio calculations were used to understand their complex structures and to explain their complexation mechanism. We show that the huge differences observed in extraction selectivity results from a small change in the complexation of nitrate counter‐ions caused by the different orientation of one methyl group in the backbone of the extractant. The obtained results give a significant new insight into metal–ligand complexation mechanisms, which will promote the development of more efficient separation techniques. Abstract : Extracting an advantage : Two diastereomers of Me2 ‐TODGA (see figure) show an extraordinary change in the extraction efficiency of trivalent f elements and even an unprecedented inversion of the selectivity for Am/Cm. These differences result from a change in the complexation of nitrate counter‐ions caused by the different orientation of just one methyl group in the backbone of the extractant. The results are supported by EXAFS analysis and by DFT‐based ab initio calculations.